PENGETAHUAN DAN STIGMA SOSIAL MEMENGARUHI PERILAKU PENCARIAN PENGOBATAN TUBERKULOSIS - Arisonang Hutagalung; Ismail Efendy; Juliandi Harahap (Jurnal Keperawatan Priority, 2022)
Knowledge and social stigma can influence the behavior of TB sufferers in seeking treatment in order to free themselves from the disease and obtain health recovery. This study aims to analyze the effect of knowledge and social stigma of tuberculosis on treatment-seeking behavior. This research is quantitative research conducted in the working area of ​​Hutabaginda Public Health Center, North Tapanuli Regency. The sample in the study was 60 people consisting of 30 TB patients and 30 people from the community. Research data in the form of primary data, secondary data, and tertiary data. Data were analyzed by univariate, bivariate, and multivariate analysis. The results showed that there was no effect of patient knowledge on the behavior of seeking treatment for tuberculosis patients with p = 0.563 > 0.05. There is no influence of internal stigma on the behavior of seeking treatment for tuberculosis patients with a p-value = 0.565 > 0.05. There is an influence of public knowledge on the behavior of seeking treatment for tuberculosis patients with a p-value = 0.027 <0.05. There is an influence of external stigma on the behavior of seeking treatment for tuberculosis patients in the working area of the Hutabaginda Public Health Center, North Tapanuli Regency with p = 0.030 <0.05. Based on this, it is recommended that the results of this study be used as input for the Hutabaginda Public Health Center, North Tapanuli Regency to make programs and evaluations in dealing with health problems, especially cases of pulmonary TB.